ECT DAMAGE INDICATES STM DIVIDED INTO STM CONTROL & LTM TRACES: NEUROLOGICAL DEFINITION OF "CONFUSION" - Eugen Tarnow (Peoples' Friendship University of Russia (RUDN University), 2017)
Recently it was shown that short term memory (STM) free recall consists of two stages: the first few recalls empty working memory and a second stage, a reactivation stage, concludes the recall (Tarnow, 2015; for a review of the theoretical predictions see Murdock, 1974). Bayley et al (2000) investigated free recall in people who had undergone Electroconvulsive therapy (ECT) and found that both recency and primacy effects were normal. Here I investigate this further, and argue that this finding suggests a division of STM between STM Control and long term memory (LTM) traces and that STM Control is not effected by ECT.Serial position probabilities from an investigation of Bayley et al (2000) were used to compare 11 subjects with ECT treatments to a control group and to a group of Alzheimer's subjects.The free recall probabilities are found to be separable into the serial position curves and the overall probability of recall. This suggests that STM is separable into an STM Control structure (the serial position curve responsible for working memory and reactivation functions) and LTM traces (the overall probability of recall).Using the ECT review of Abbott et al (2014a) showing excess activity in MTL and lacking activity in the frontal lobes I suggest that STM Control is overworked trying to establish stable patterns in LTM. It could be that the confusion resulting from ECT is due to the failure of this process, suggesting a neurological definition of confusion.